Person-centered strategies for integrating TB treatment into community pharmacies for people with TB/HIV in Uganda: A human-centered design methodology study protocol - Jonathan Izudi; Adithya Cattamanchi; Christine Sekaggya-Wiltshire; Rachel King; Noah Kiwanuka; Amanda Sammann (Plos one, 2026)
Background: Community pharmacies (private retail drug shops or pharmacies) have successfully delivered antiretroviral therapy (ART) to people with human immunodeficiency virus (HIV) and could support integrated tuberculosis (TB) treatment, but the implementation strategies are unclear. To inform a planned pilot randomized trial, we aim to develop person-centered strategies for integrating TB treatment into community pharmacies targeting people with TB/HIV using a Human-Centered Design (HCD) methodology. Here, we describe the study protocol. Methods: We will employ a three-phased HCD methodology comprising inspiration, ideation, and implementation across six primary health facilities in Kampala, Uganda. Eligible participants will include people with TB/HIV, focal persons for TB and HIV, Ministry of Health officials, and community pharmacy healthcare providers. The inspiration phase will build the themes on barriers and facilitators to integrating TB treatment into community pharmacies from a qualitative study, complemented by participant observations at selected 2–3 community pharmacies to understand the care pathway of people with TB/HIV (journey mapping), including sketching the ideal pharmacy-based TB treatment pick-up. The ideation phase will use design workshops to consolidate identified themes, generate insight statements, including translating them into design opportunities, and conclude with forming low and high-fidelity prototypes. The implementation phase will comprise two rounds of prototype testing, low and high fidelity, with 12–16 participants per round, including people with TB/HIV, focal persons, Ministry of Health officials, and pharmacy health workers. Feedback on usability, desirability, feasibility, and viability will guide iterative refinement, with high-scoring prototypes in system usability surveys prioritized for trial. Discussion: Through iterative user engagement, we will adapt contextually relevant strategies that will leverage key facilitators and address barriers to TB treatment integration. Strategies demonstrating perceived usefulness, user-friendliness, high acceptability, person-centeredness, and contextual relevance will be adapted and piloted in a planned randomized trial aiming to determine feasibility, acceptability, and fidelity, including preliminary effectiveness.
Keywords: Community pharmacies; Person-centered strategies; TB treatment; TB/HIV; Uganda